Perceptions of Chinese university English majors on the use of WeChat as a platform for peer feedback in English writing - Shi, Sun; Razali, Abu Bakar; Ab Jalil, Habibah; Ismail, Lilliati (Sciedu Press, 2024)
Peer feedback is widely acknowledged as a valuable addition to English language learning, with several research confirming its various benefits in improving English writing skills (Liu & Edwards, 2018). WeChat is the main communication tool in China, especially among young people. However, its potential for peer evaluation in English writing has not been thoroughly explored especially for English language learning, and more specifically for giving and receiving peer feedback for English writing. Current research mostly centers on Chinese college students, neglecting English majors who have comparable difficulties in mastering English writing abilities (Gan et al., 2004). Therefore, this study aims to investigate the perceptions of Chinese English majors on using WeChat for peer feedback. Data was gathered using a structured questionnaire that was designed based on the Technology Acceptance Model (TAM). The results show that most respondents have a good attitude towards using WeChat for peer feedback. Respondents have positive views on the platform's effectiveness in enabling peer feedback, along with factors like output quality, results demonstrability, and perceived ease of use. Participants also positively view aspects, such as external control, behavioral intention, voluntariness, and perceived enjoyment in using WeChat for peer feedback in English writing. Integrating WeChat as a peer feedback platform is considered beneficial for enhancing the teaching-learning process, which is important for educators and curriculum designers. The researchers posit that the use of WeChat as a platform can facilitate peer feedback for students’ English writing learning as a second language teaching tool as it shows the potential to improve the effectiveness of English education whilst also promoting the use of technology outside the classroom for peer feedback and interactive English language learning.